Optimalisasi Penggunaan Masker pada Anak di Era Pandemi Covid-19 melalui Metode Storytelling di TK Mawar Gambut - Chandra Chandra; Meilya Farika Indah; Eddy Rahman; Ahmad Zacky Anwary; Asrinawaty Asrinawaty; Zuhrupal Hadi; Norsita Agustina (Jurnal Abdimas Kesehatan (JAK), 2022)
Kindergarten (TK) education is an early stage of education as children who are experiencing a developmental transition really need an approach that can overcome the problems experienced, one of which is implementing the COVID-19 pandemic health protocol such as the use of good and correct masks. The purpose of this activity is to help improve social skills such as communication skills, through community service, community empowerment programs at Mawar Kindergarten, Gambut District through storytelling with a focus on doing fairy tales to children in order to be able to respond to the use of masks properly and correctly. The method of this activity is a fairy tale through storytelling to students with the title "Say No to the Covid-19 Virus, Let's Wear a Mask" then after telling the story the children are chosen to be Covid-19 Exterminator Heroes. The design of a storytelling program by involving children in Mawar Kindergarten so as to increase children's awareness in the use of masks is good and right. Consider to revise the structurethat children can and understand how to follow health protocols, especially the use of good and correct masks and good hand washing using storytelling. The conclusion of this community service activity is that children and even teachers are able to make changes in behavior towards the use of masks to avoid being exposed to covid-19.